2004
DOI: 10.1093/carcin/bgh180
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin causes cell cycle arrest and apoptosis in human bladder transitional cell carcinoma cells by regulating CDKI-CDK-cyclin cascade, and caspase 3 and PARP cleavages

Abstract: Bladder cancer is the fourth and eighth most common cancer in men and women in the USA, respectively. Flavonoid phytochemicals are being studied for both prevention and therapy of various human malignancies including bladder cancer. One such naturally occurring flavonoid is silibinin isolated from milk thistle. Here, we assessed the effect of silibinin on human bladder transitional cell carcinoma (TCC) cell growth, cell cycle modulation and apoptosis induction, and associated molecular alterations, employing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 31 publications
3
68
1
3
Order By: Relevance
“…Likewise, silibinin-fed SCID mice injected with SN12K1 cells exhibited a reduction in tumor size (54). Consistent with these results, several studies have shown that silibinin inhibits growth as well as induces apoptosis in several urinary bladder cancer cell lines which were associated with an increase in p53 expression, downregulation of survivin, cyclin D1, ERK1/2 phosphorylation and nuclear phospho-p65, cleavage of caspases, PARP, and Cip1/p21, and mitochondrial release of cytochrome c, Omi/HtrA2, and apoptosis-inducing factor (55)(56)(57)(58)(59)(60). This silibinin-mediated inhibition was also observed in rat models of urinary bladder cancer reducing lesions (60).…”
Section: Broad Spectrum Cancer Chemopreventive Efficacy Of Silibininsupporting
confidence: 63%
“…Likewise, silibinin-fed SCID mice injected with SN12K1 cells exhibited a reduction in tumor size (54). Consistent with these results, several studies have shown that silibinin inhibits growth as well as induces apoptosis in several urinary bladder cancer cell lines which were associated with an increase in p53 expression, downregulation of survivin, cyclin D1, ERK1/2 phosphorylation and nuclear phospho-p65, cleavage of caspases, PARP, and Cip1/p21, and mitochondrial release of cytochrome c, Omi/HtrA2, and apoptosis-inducing factor (55)(56)(57)(58)(59)(60). This silibinin-mediated inhibition was also observed in rat models of urinary bladder cancer reducing lesions (60).…”
Section: Broad Spectrum Cancer Chemopreventive Efficacy Of Silibininsupporting
confidence: 63%
“…Exposure to silibinin resulted in a G1 arrest in human bladder transitional cell carcinoma cells (McDonald et al, 2000) and human prostate cancer DU145 cells (Owa et al., 2001). Silibinin treatment aslo inhibited human nonsmall cell lung cancer (NSCLC) cells growth and targeted cell-cycle progressing causing a prominent G1 arrest in dose-and time-dependent manner (Tyagi et al, 2004), but combinations with histone deacetylase inhibitors (HDACi) exhibited a significant G 2/M arrest of the NSCLC cells . Silibinin caused G1 and G2/M cell cycle arrest in human prostate cancer PC3 cells (Mateen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…1A). Accumulating evidence indicates that silibinin has anticancer activity in various tumor cells, including cancers of prostate (5)(6)(7)(8)(9), breast (10,11), skin (12), colon (13), lung (14), kidney (15,16), and bladder (17)(18)(19)(20). There is increasing interest in elucidating the mechanisms of action for silibinin as an effective agent for chemoprevention and chemotherapy against various types of cancers.…”
Section: Introductionmentioning
confidence: 99%